Macrolide resistance genes and mobile genetic elements in waterways from pig farms to the sea in Taiwan. (June 2022) - Suzuki, Satoru; Kadoya, Aya; Masuda, Nagi; Sugimoto, Yuta; Takada, Hideshige; Mizukawa, Kaoruko; Takei, Ayaka; Chou, Hsin-Yiu; Wu, Jer-Horng
Highlights: Pig farm wastewater in Taiwan showed a high rate of erythromycin-resistant bacteria. Seawater was less contaminated with the resistant bacteria. Aquaculture ponds separated from pig farms have few macrolide resistance genes. IntI1 was abundant in pig farms, rivers, and aquaculture ponds. IntI1 was positively related to mef (A), erm (B), and mph (B) but not mef (C)- mph (G). ABSTRACT: Objectives: Macrolides have a long history of use in animals and humans. Dynamics of macrolide-antibiotic resistance genes (ARGs) in waterways from the origin to the sea has not been reported. Methods: Resistant bacterial rate was measured by culture method, and copy numbers of macrolide-ARGs, mef (A), erm (B), mph (B), mef (C)- mph (G), and mobile genetic elements (MGEs) traI and IntI1 were quantitated in environmental DNA. Community composition in each site was investigated by 16S rRNA gene metagenomic sequencing. In Yilan area, antibiotics were quantitated. Results: Surface water samples from pig farms to the sea in southern and northern areas in Taiwan were monitored. Macrolide-resistant bacteria accounted for 3%–28% of total colony-forming bacteria in aquaculture ponds and rivers, whereas in pig farm wastewater it was 26%–100%. Three common macrolide-ARGs mef (A), erm (B), and mph (B) and the relatively new mef (C)- mph (G) were frequently detected in pig farms, but not in aquaculture ponds and the sea. Rivers receiving pig wastewater showed ARG contamination similar to the pig farms. Among the MGEs, IntI1 was frequently distributed in all sites and was positively related to mef (A), erm (B), and mph (B) but not to mef (C)- mph (G). Conclusion: Pig farms are the origin of macrolide-ARGs, although macrolide contamination is low. Since lincomycin was detected in pig farms in the northern area, the increase of macrolide-ARGs is a future concern due to cross-resistance to lincomycin. ARGs abundance in aquaculture ponds was low, though MGEs were detected. Relation of IntI1 to ARG suggests convergence of ARGs to specific MGEs might be time/history dependent. Graphical Abstract: Image, graphical abstract